Which Procedure Yields Better Outcomes: Sleeve Gastrectomy, Roux-en-Y Gastric Bypass or Mini Gastric Bypass? Seven Years Outcome Analysis - Ahmet Can Sari; Mehmet Alperen Avci; Sonmez Ocak; Can Akgun; Omer Faruk Buk; Ahmet Burak Ciftci; Emin Daldal (Medicina)
Background and Objectives: Bariatric surgery is the most effective method for achieving sustainable weight loss, improving quality of life, and resolving obesity-related comorbidities over the long term. However, data from long-term studies remain scarce and contradictory. Materials and Methods: This study is a retrospective analysis of prospectively collected data over a 7-year follow-up period involving 211 patients diagnosed with morbid obesity who underwent sleeve gastrectomy (SG), Roux-en-Y gastric bypass (RYGB), or mini gastric bypass (MGB) at Samsun University Training and Research Hospital, Department of General Surgery, between 1 January 2014 and 1 January 2018. Changes in weight, remission of associated comorbidities, postoperative complications, re-admission rates, and revision requirements were compared among the patients. Results: Of the 211 patients, 20.4% were male, and 79.6% were female. During the study period, 61.1% of patients underwent SG, 29.4% underwent MGB, and 9.5% underwent RYGB. There was no statistically significant difference among the three surgical techniques in terms of weight change parameters, comorbidity remission, postoperative complications, and readmission rates. However, revision rates were significantly higher among patients who underwent SG (p < 0.05). Conclusions: SG, MGB, and RYGB techniques are comparable and reliable methods in terms of long-term weight loss, surgical outcomes, and complications. After a 7-year follow-up period, all three techniques were found to be similar in terms of HT, T2DM, and GERD remission; however, SG was observed to have a higher revision requirement compared to the other surgical techniques.